Forensic print extraction using 3D technology and its processing. - Rajeev, Srijith.; Kamath K.M., Shreyas.; Panetta, Karen.; Agaian, S. S. (Tufts University. Tisch Library., 2017)
Biometric evidence plays a crucial role in criminal scene analysis. Forensic prints can be extracted from any solid surface such as firearms, doorknobs, carpets and mugs. Prints such as fingerprints, palm prints, footprints and lip-prints can be classified into patent, latent, and three-dimensional plastic prints. Traditionally, law enforcement officers capture these forensic traits using an electronic device or extract them manually, and save the data electronically using special scanners. The reliability and accuracy of the method depends on the ability of the officer or the electronic device to extract and analyze the data. Furthermore, the 2-D acquisition and processing system is laborious and cumbersome. This can lead to the increase in false positive and true negative rates in print matching. In this paper, a method and system to extract forensic prints from any surface, irrespective of its shape, is presented. First, a suitable 3-D camera is used to capture images of the forensic print, and then the 3-D image is processed and unwrapped to obtain 2-D equivalent biometric prints. Computer simulations demonstrate the effectiveness of using 3-D technology for biometric matching of fingerprints, palm prints, and lip-prints. This system can be further extended to other biometric and non-biometric modalities. © (2017) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE)